Juridical Review on Grants of Treasure Together Of Child Due Divorce In Religious/ Islamic Courts of Kendal - Bagus Malik Hakim; Akhmad Khisni; Munsharif Abdul Chalim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
Divorce in the event, then the entire joint property, the property acquired during the marriage is divided into two parts, namely the upper half of the husband and half to the wife. Kendal Religious Court in deciding the division of joint property, there are in accordance with the provisions of Islamic Law Compilation, is half portion for half of the husband and wife to. But there is also, Kendal Religious Courts decide part of the joint property of the wife is greater, which is part of the joint property to the wife more than in the joint property of the husband. There is also, the Religious Courts Kendal cut off all joint property is granted (given) to his son.The purpose of this research are: 1) To know and understand the implementation of joint property grants to children of divorce in the Religious Kendal. 2) To know and understand the considerations related decision Religious Court judges Kendal in community property donated to the children of divorce. 3) To know and understand the barriers and solutions implementation of joint property grants to children of divorce in the Religious Kendal. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by descriptive analytical method.Kendal Religious Court Decision on the Implementation of the Joint Grant Treasure Kids Due To Divorce Court Kendal Religion is a decision that truly reflects the sense of justice, reflect expediency and legal certainty. Therefore, when the divorced husband and wife agreed to grant the joint property willed to his son, accompanied by a deed of peace. Therefore, the verdict ideal is when it contains elements of Gerechtigekeit (justice), Zweckmassigkeit (benefit), and Rechtssicherheit (rule of law) in proportion.Keywords: Overview of Juridical; Grant; Treasure Together; Divorce.